PERSEPSI WISATAWAN TERHADAP KAWASAN WISATA PANTAI LABOMBO DI KOTA PALOPO - Bibin, Muhammad (Fisheries Science Study Program, Faculty of Science and Technology, Muhammadiyah University of Sidenreng Rappang., 2021)
Labombo Beach as a beach tourism object saves quite a variety of attractions. Recreational beach tourism activities are the most dominant type of activity at Labombo Beach. Recreational activities utilize coastal resources such as white sand, stretches of beach, views and coastal waters. Tourism potential in Labombo Beach is fully managed by the Regional Government, both preparing the management of alternative areas with interesting objects and attractions, thus affecting the interest / motivation of visiting tourists. This study aims to describe the perceptions of tourists regarding the Labombo Coast Area in Palopo City. Sampling in this study was carried out to tourists visiting the Labombo Coast Area as many as 30 people using the accidental sampling method. Data were collected using questionnaires and analyzed through descriptive analysis. The results showed that tourists' perceptions of Labombo Beach were very good in terms of facilities, comfort, safety and natural scenery. According to visitors' perceptions of transportation facilities to Labombo Beach tourist sites is still lacking, as seen from 87% of visitors said that the transportation facilities were lacking, and as many as 13% of visitors said enough. This is due to the lack of public transportation to tourist sites, although there are public transportation such as taxis in general, the fees charged are expensive for visitors.